RECOVERY OF RICHNESS, BIOMASS AND DENSITY IN ATLANTIC RAINFOREST AREAS AFTER CLEARCUTTING - Cardoso-Leite, Eliana; Devides Castello, Ana Carolina; Coelho, Samuel; Coelho, Juliana Costa; Schievenin, Dimitrio Fernandes [UNESP]; Carmo, Janaina Braga do (Univ Federal Vicosa, 2016)
Our aim was to analyze areas of Atlantic rainforest after clearcutting with different types of management (pasture establishment followed (PA) by abandonment and simple abandonment (NR)). We then compared composition parameters, structure and ecological processes with native forest as a reference. Our study was conducted in Sete Barras municipality, Sao Paulo State, Brazil. Data collection was performed six years after clearcutting, including all woody plants found in two strata (DBH (diameter at 1.3 m soil) >= 5cm and DBH <5cm and height >= 1.5m, respectively). PA and RN showed lower values of richness, density, basal area, and diversity index (H') when compared with F for both strata. Thus, independently of management type, six years of abandonment were not enough to recover the parameters analyzed, compared to native forest. Type of management influences ecological succession and structural parameters considering the second strata only.
Keywords: Abandoned pasture; Ecological succession; Natural regeneration